"Of course, cooperation first": the effect of subsidiary capability and perception gaps for subsidiary development. Issue 3 (13th May 2020) - Chen, Lu-Jui; Tsou, Hung-Tai
Abstract : Purpose: This study aims to discuss not only the relationship between performance and cooperation but also discusses whether a subsidiary should prioritize performance above cooperation or whether a subsidiary should prioritize cooperation above performance. In addition, because the headquarters-subsidiary relationship influences the subsidiaries, the perception gaps (PGs) between headquarters and subsidiaries are taken as moderators to explore when there are perception differences between headquarters and subsidiaries and the effect on the relationship between subsidiaries' cooperation (SCO) and performance (SP). Design/methodology/approach: This study obtained the data through a survey of 170 subsidiaries in China; chief executive officer or senior managers were selected as the data collection sources. AMOS analysis was used to address sophisticated data analysis issues. Findings: The empirical evidence indicates that subsidiary capabilities have direct impacts on SCO and SP. In addition, SCO and performance have mediating effects. More specifically, SCO has a full mediating effect and SP has a partial mediating effect. For the moderating effects, the PG weakens the effect of SCO on SP. Originality/value: This study contributes to the literature on subsidiary capabilities by offering a headquarters-subsidiary relationship model. As both the conceptual and empirical research studies on this topic are still underdeveloped, the study provides fresh insights into collaborative management and offers significant theoretical and managerial implications. Specifically, this study focuses on the impacts that subsidiary capabilities and PG have on cooperation and performance.